Multiloculated hydrocephalus in an adult: Role of MRI FIESTA sequence in diagnosis and management - Ramli, N.; Fadzli, F.; Muthusamy, K.A.; Hong, C.K. (ASEAN Neurological Association, 2014)
This is a case of an adult patient with hypertensive intraventricular haemorrhages complicated by hydrocephalus that failed to respond to endoscopic third ventriculostomy (ETV). High-resolution 3D Fast Imaging Employing Steady State Acquisition (FIESTA) magnetic resonance imaging (MRI) revealed underlying multiloculated hydrocephalus. This case report highlights the appropriate sequence and its attributes that offer adequate preoperative information detailing the ventricular system.